The nutritional status of students at the University of the Philippines (Diliman Campus) as determined by anthropometric and biochemical methods and health questionnaire - Rueda, Josefina U. (College of Home Eonomics, University of the Philippines Diliman, 1979)
This thesis is part of a general study on the nutritional status of college students at the University of the Philippines, Diliman, Quezon City, with emphasis on the role of the University Food Service. This study in particular is concerned with the assessment of the students' nutritional status using weigh, height and hemoglobin level as the primary nutritional status indicators. The correlates of these indicators were also determined. A total of 3, 149 students composed of the sample. Results indicate a low percentage of weight problems among the subjects. Incidence of anemia was also low. Health questionnaire responses, used to support nutritional status indicators indicated frequent incidence of all illnesses among a very small percentage of the subjects. Some students with nutritional problems claimed to have manifested behavioral symptoms negatively affecting learning. In this connection, claims of listlessness and fatigue were found to be closely associated. Age, sex, energy and protein intake were found to be significantly and positively related to height, weight, hemoglobin level and nutritional status rating. However, the results of nutritional status assessment, specifically using height, weight and hemoglobin levels as indicators, depended primarily on the standards or reference points used, i.e., results differed depending on the standards or reference used. Recommendations are made for the extension of health and nutrition-related services among students with weight problems and those suspected to be suffering from anemia and also for the promotion of preparation and consumption of more iron-rich foods in the University Food Service outlets. Finally, in the absence at present f real standard weights of adolescent Filipinos, it is recommended that Tannhauser formula to be used as a quick measure in deriving the ideal or "standard" weights using an adjustment of 15% instead of the commonly used 10%.